Socialization of Marriage Law During the Iddah Period and Efforts to Increase Public Understanding of Islamic Law at the Nurul Iman Cikarang Pusat Ta'lim Assembly - Adzillani Tahta Arsyika; Winda Sri Rahayu; Salwa Halimatus Sa’diyah; Oyoh Bariah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This iddah period legal socialization activity aims to increase public understanding, especially the congregation of the Central Cikarang Taklim Nurul Iman Council, about the importance of obeying Islamic law. The material presented includes the meaning, legal basis, types of iddah, prohibitions during the iddah period, as well as legal sanctions for marrying a woman during the iddah period. The method used is a simple lecture with support in the form of modules as learning media, which makes it easier to deliver material to congregations with diverse educational backgrounds. Group discussions are an important part of this activity, which encourages active congregational participation through questions and responses to the material presented. The results of the activity showed that this socialization was successful in increasing the congregation's understanding of the laws of the iddah period, which could be seen from their enthusiasm in participating in discussions and asking questions. Factors supporting the success of this activity include moral support from the surrounding community, adjustments to the regular weekly recitation schedule, the congregation's trust in the assembly, and the contribution of a solid implementation team. This activity not only supports the achievement of the implementing team's academic goals, but also has a positive impact in building awareness of the congregation regarding the importance of complying with Islamic law as a guideline in social life.